Persaingan Bisnis: Telaah Konsep Pemikiran Kahrudin Yunus - Nuradi, Nuradi; Khatimah, Husnul; Wulan, Elis Ratna (ITB AAS INDONESIA Surakarta, 2024)
This research discusses current business competition practices which tend to have a negative connotation, namely unhealthy competition and bringing each other down. The aim of the research is to provide an overview and paradigm regarding the true meaning of the word competition. In this research the researcher used a literature review method or literature review which focuses on collecting past data, especially the opinions of economic experts, in this case Kahrudin Yunus, who he wrote about in his book